Maintaining the native gut microbiota of bharal (Pseudois nayaur) is crucial in ex situ conservation - Gao, Hongmei; Chi, Xiangwen; Song, Pengfei; Gu, Haifeng; Xu, Bo; Cai, Zhenyuan; Jiang, Feng; Li, Bin; Zhang, Tongzuo (Frontiers in Microbiology, 2024)
As wildlife protection continue to strengthen, research on the gut microbiota of wildlife is increasing.Carrying out conservation and research on endangered species in the Qinghai Tibet Plateau plays an important role in global biodiversity conservation. This study utilized 16S rRNA sequencing of fecal samples to investigate the composition, function, and changes of the gut microbiota of bharal in different environments, seasons, and genders. The results showed that Firmicutes and Bacteroidota were the dominant phyla and UCG-005, Bacteroides, UCG-010 were the dominant genera of bharal.In the wild, the abundance of Firmicutes increased which was conducive to the decomposition and utilization of cellulose, hemicellulose, and carbohydrate. Due to the variety of food types and nutrition in different seasons, the composition and function of gut microbiota were obviously different between genders. Compared with zoo, higher alpha diversity, a more complex gut microbiota network structure, 2 and stronger metabolic function were conducive bharal to adapting to the wild environment. In the zoo, captive bharals were fed foods rich in high fat and protein, which increased the abundance of Bacteroidota and reduced the alpha diversity of gut microbiota. A fixed diet unified the gut microbiota between genders of bharal. It is very important to pay attention to the impact of captive environments and maintain the native gut microbiota of wildlife.